2016
DOI: 10.1177/1753465816628800
|View full text |Cite
|
Sign up to set email alerts
|

Malignant pleural mesothelioma: an update on diagnosis and treatment options

Abstract: Malignant pleural mesothelioma (MPM) represents a significant diagnostic and therapeutic challenge and is almost always a fatal disease. Imaging abnormalities are common, but have a limited role in distinguishing mesothelioma from metastatic pleural disease. Similarly, minimally invasive biomarkers have shown promise but also have limitations in the diagnosis of mesothelioma. In experienced centers, cytology and immunohistochemistry are now sufficient to diagnose the epithelioid subtype of mesothelioma, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 94 publications
0
41
0
5
Order By: Relevance
“…The optimal management for MPM is still debated, but up to now, cisplatin and pemetrexed-based chemotherapy (CT) is considered the standard of care, since randomized controlled trial (RCT) have reported its superiority in terms of survival and quality of life, compared to cisplatin alone (7,8). Administration of induction/adjuvant systemic CT has become the standard of care in case of any surgical procedure with curative intent (9).…”
Section: Introductionmentioning
confidence: 99%
“…The optimal management for MPM is still debated, but up to now, cisplatin and pemetrexed-based chemotherapy (CT) is considered the standard of care, since randomized controlled trial (RCT) have reported its superiority in terms of survival and quality of life, compared to cisplatin alone (7,8). Administration of induction/adjuvant systemic CT has become the standard of care in case of any surgical procedure with curative intent (9).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that malignant pleural mesothelioma develops after long-term exposure to asbestos and is a highly aggressive neoplasm with a poor prognosis. [1][2][3][4] Because a large number of epithelioid mesothelioma cases show a tubulopapillary, tubular or solid pattern, it is sometimes difficult to distinguish epithelioid mesothelioma from other neoplastic diseases, such as pseudomesotheliomatous pulmonary carcinomas, metastatic carcinomas originating from distant organs, and reactive hyperplasia of the pleura. 5,6 To date, the most common problem in the diagnosis of mesothelioma has been to differentiate it from pulmonary adenocarcinoma and metastatic adenocarcinoma from other organs.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant pleura mesothelioma (MPM) is an occupational-related form of cancer of the thoracic cavity and remains a diagnostic and therapeutic challenge [1,2]. Mesothelioma arises from the pleura in 70-90% [1][2][3][4] and from the peritoneum in 10-30% of the cases [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mesothelioma arises from the pleura in 70-90% [1][2][3][4] and from the peritoneum in 10-30% of the cases [5]. Rarely it can arise from testicles (<1%) [6] or the pericardium (<1%) [7].…”
Section: Introductionmentioning
confidence: 99%